Yield of early yellow potato cultivars (Solanum tuberosum L.) of the Phureja group - Seminario-Cunya, Juan F.; Villanueva-Guevara, Roiser; Valdez-Yopla, Misael H. (Agronomía Mesoamericana, 2018)
The group Phureja (Solanum tuberosum L.) has been little studied in Peru, despite its culinary, nutritional and industrial quality and the risk of erosion to which it is subjected in recent decades. The objective of this research was to evaluate the total and commercial yield of tubers of fifteen potato cultivars (Solanum tuberosum, Phureja group). Traditional, yellow, and early cultivars were evaluated from Cajamarca region, Peru, to identify the most productive cultivars within the study group. The work was carried out on a plot of the Silvoagricultural Service of the Universidad Nacional de Cajamarca: 7 ° 10`LS and 78 ° 30’ LW, 2670 masl, 14.7 °C average annual temperature, 64.5% relative humidity and 651 mm of annual precipitation. Seeding was carried out at 0.90 m and 0.40 m between rows and between plants, respectively; in completely randomized block design, with three repetitions. Plant height, number of stems, number and total weight of tubers, number and weight of tubers according to categories, specific gravity, dry matter of tubers and foliage, and harvest index were evaluated. Significant statistical differences were found between cultivars for a total number of tubers, number of commercial tubers, a weight of commercial tubers, plant height, number of stems, dry matter of the tubers and harvest index. The best cultivars in tuber yield were Blanca amarilla (27.8 t/ha), Limeña huachuma (27.4 t/ha), Llanqueja (25.0 t/ha), Amarilla redonda (23.3 t/ha) and Piña amarilla (21.8 t/ha).